A Survey of Common Therapeutic Facilities Available in Soccer Coaching; Soccer Coaches Perspective - David D, Jayarajan (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The purpose of the study was to find out a survey of common Therapeutic Facilities Available in Soccer Coaching. The subjects for the purpose of the study were selected from the Zonal and All India Inter- University football championship. The total respondents of the study were 20 (Inter-University Football coaches). The survey method was used in conducting the study. The questionnaire were framed and prepared in consultation with many experts. The percentage was calculated for each response to the data for the purpose of the present study. The study observed that 68.75% of soccer coaches had expressed Less availability of sports medicine expert, 48.75% expressed Lack of advanced therapeutic modalities, 38.75% expressed Poor consultation and diagnosis in treating and rehabilitation of injuries, 31.25% expressed Poor guidance from coaches in preventing and rehabilitation of injuries and 25% expressed Too much time is consumed in treating injuries in treating injuries in our country, 100% of soccer coaches were not satisfied with the facilities available in the country for the treatment of soccer injuries, the available sources for adopting for their players in faster recovery from training were Physiotherapy (40%), Consultation with general doctor (10%), Consultation with specialist (10%) and Therapeutic exercises (65%), 100% of soccer coaches had expressed that their players use protective gears.